Changes in cellular antioxidant and anti-inflammatory activity after 12 months storage of roasted maize-based beverages supplemented with nejayote solids. (September 2019) - Buitimea-Cantúa, Nydia E.; Antunes-Ricardo, Marilena; Villela-Castrejón, Javier; Gutiérrez-Uribe, Janet A.
Abstract: The aim of this study was to evaluate changes in color, calcium, bound and free hydroxycinnamic acids content, as well as, the in vitro anti-inflammatory and cellular antioxidant activities of maize-based beverages enriched with nejayote solids that were stored for 12 months at 25 °C. Maize-based beverages enriched with nejayote solids (BENS) at different concentrations (3, 6 or 9%, w/w) were formulated. Nejayote solids addition increased the bound and free ferulic, p -coumaric, dehydro-diferulic and dehydro-triferulic acids contents in maize-based beverages. Maize beverage enriched with 9% of nejayote solids exhibited higher calcium content (340.66 mg/100 g), cellular antioxidant activity (59.8%) and nitric oxide inhibition (95.78%) respect to control beverage. Storage time drastically decreased the anti-inflammatory activity of the maize-based beverages enriched with nejayote. This effect was more pronounced in BENS-3% whose anti-inflammatory potential decreased 70% after 12- months of storage. BENS-9% showed the best phytochemicals profile, anti-inflammatory activity, cellular antioxidant activity, and calcium content and was the most stable during storage time. Nejayote can be used as a functional ingredient for the production of maize-based beverages incorporated with nejayote solids rich in calcium, ferulic acid, anti-inflammatory, and antioxidant activity. Graphical abstract: Image 1067 Highlights: Nejayote addition increased phenolic acids contents in corn-based beverages. Nejayote addition increased calcium content in corn-based beverages. Nejayote addition increased the cellular antioxidant and anti-inflammatory activities. After 12 months-storage, phenolic acids content was lower in corn-based beverages. After 12 months-storage, decreased the cellular antioxidant and anti-inflammatory activities.